Peningkatan Kapasitas dan Kualitas Hidup Masyarakat Bangsri dalam menghadapi New Normal - Fauzi, Umar (Bisma : Bimbingan Swadaya Masyarakat, 2023)
Miftahul 'Ula Islamic High School (STAIM) Nglawak Kertosono Nganjuk, as one of the higher education institutions that develops science, technology, information and the arts that breathe Islam, has a great responsibility in realizing and succeeding national development, especially development in the field of religion, spiritual mentality, social welfare and education by not forgetting other fields. The method used is PAR (Participatory Action Research). The results of the assistance In the implementation of KPM-IK participation activities is a work program that is important but in its implementation is not very emphasized and 98% carried out. This program is carried out thanks to the assistance and good cooperation from many parties, both from KPM-IK members themselves, community members, village governments or other institutions. Quality targets are achieved but in quantity some programs are still not in line with expectations.